1982
DOI: 10.1128/aem.44.4.972-987.1982
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine resistance patterns of bacteria from two drinking water distribution systems

Abstract: Hitachi model 100-20 spectrophotometer) of 0.01 to 0.02 and a cell concentration (using E. coli strain no.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(90 citation statements)
references
References 30 publications
5
79
0
3
Order By: Relevance
“…The observed increase may be due to increased proportions of non-cultivable target bacteria with assayable activity (Davies et al 1995b ;Nwoguh et al 1995) and presence of b-D-galactosidase-positive, nontarget micro-organisms (Davies et al 1995a ;Fiksdal et al 1997 ;Van Poucke and Nelis 1997) that are more resistant to chlorine than FC bacteria, e.g. Bacillus (Ridgway and Olson 1982). The more similar reductions in enzyme activity and number of cultivable FC of sewage vs chlorine dose when injured FC were recovered indicated that an important portion of the b-D-galactosidase activity was related to viable, injured FC bacteria.…”
Section: Enzyme Activitymentioning
confidence: 99%
“…The observed increase may be due to increased proportions of non-cultivable target bacteria with assayable activity (Davies et al 1995b ;Nwoguh et al 1995) and presence of b-D-galactosidase-positive, nontarget micro-organisms (Davies et al 1995a ;Fiksdal et al 1997 ;Van Poucke and Nelis 1997) that are more resistant to chlorine than FC bacteria, e.g. Bacillus (Ridgway and Olson 1982). The more similar reductions in enzyme activity and number of cultivable FC of sewage vs chlorine dose when injured FC were recovered indicated that an important portion of the b-D-galactosidase activity was related to viable, injured FC bacteria.…”
Section: Enzyme Activitymentioning
confidence: 99%
“…Sections of biofilms in distribution systems can periodically break off and enter the bulk water (Daly et al 1998;Stoodley et al 2002). Microbial aggregates in the water are protected from exposure to chlorine disinfectants by the same mechanisms that protect microorganisms in biofilms, even in systems with a relatively constant disinfectant residual (Ridgway and Olson 1982;U.S. Environmental Protection Agency 1992;Szewzyk et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is not known why these organisms should predominate, and while adaptation or resistance mechanisms could be involved, pseudomonads are ubiquitous in the environment and staphylococci are most likely to originate from skin squames shed by food operatives. The industry also recognizes that micro-organisms adhered to surfaces are more resistant to disinfectants than those in suspension (Ridgeway and Olsen 1982;Hugo et al 1985;Le Chevalier et al 1988;Frank and Koffi 1990;Wright et al 1991;Dhaliwal et al 1992;Ronner and Wong 1993;Andrade et al 1998). Similarly, micro-organisms are better able to resist disinfectants at the low temperatures associated with high risk, chilled food production (Taylor et al 1999).…”
Section: Introductionmentioning
confidence: 99%